2015
DOI: 10.1093/schbul/sbv014
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Measures of Craniofacial Dysmorphology in a Family Study of Schizophrenia and Bipolar Illness

Abstract: Several laboratories, including ours, have reported an overrepresentation of craniofacial (CF) anomalies in schizophrenia (SZ). How might this dysmorphology arise in a brain-based disorder? Because the brain and face derive from shared embryologic primordia and morphogenetic forces, maldevelopmental processes may result in both CF and brain dysmorphology. Our approach is 2-pronged. First, we have employed, for the first time in the study of psychiatric disorders, objective measures of CF morphology that utiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…In particular, their study reported no difference in MPAs involving the eyes between patients with BD and controls, but a significant difference between those with SCZ and controls. Similarly, another anthropometric study revealed that elevated anomalies along the junction of the frontonasal and maxillary prominence derivatives (the horizontal plane across the eyeballs, developing during embryonic days 37–55) were apparent among SCZ probands and their relatives, while anomalies in derivatives of frontonasal and mandibular embryonic primordia were associated with both SCZ and BD diagnostic groups (Deutsch et al, ). Taken together, our findings agree that MPAs measured with the Waldrop scale have some degree of specificity to SCZ (Green et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, their study reported no difference in MPAs involving the eyes between patients with BD and controls, but a significant difference between those with SCZ and controls. Similarly, another anthropometric study revealed that elevated anomalies along the junction of the frontonasal and maxillary prominence derivatives (the horizontal plane across the eyeballs, developing during embryonic days 37–55) were apparent among SCZ probands and their relatives, while anomalies in derivatives of frontonasal and mandibular embryonic primordia were associated with both SCZ and BD diagnostic groups (Deutsch et al, ). Taken together, our findings agree that MPAs measured with the Waldrop scale have some degree of specificity to SCZ (Green et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, more objective and quantitative assessment methods for MPA evaluations should be developed in addition to solely relying on the traditional ratings based on visual examination. For example, researchers have adopted geometric morphometric methods, photometric face scanning, and anthropometric measurements to analyze facial shapes, skull base width, and craniofacial morphology in patients with SCZ (Buckley et al, ; Deutsch et al, ; Hennessy, Baldwin, Browne, Kinsella, & Waddington, ; Hennessy et al, ). However, these methods still rely on a face‐to‐face evaluation that may be associated with a potential subjective bias as blinding to diagnosis is difficult.…”
mentioning
confidence: 99%
“…Below we provide a detailed description of the domestication traits commonly found in schizophrenic patients ( Fig. 1 Physical Anomalies SZ patients typically feature minor craniofacial dysmorphisms, including facial asymmetries, particularly those arising along the midfacial junctions [between frontonasal and maxillary prominence derivatives; Gourion et al, 2004, Deutsch et al, 2015, and ear shape abnormalities [including adherent ear lobes, lower edges of the ears extending backward/upward, malformed ears, asymmetrical ears, or cuspidal ears; Yoshitsugu et al, 2006;Akabaliev et al, 2011;Lin et al, 2012] are reproducibly observed in SZ patients. Some of these features (like a prominent crux of helix and ear lobe crease or a primitive shape of the ear) are considered pathognomonic for SZ in the differential diagnosis of psychotic conditions [Trixler et al, 2001;Praharaj et al, 2012].…”
Section: Domestication Features In Szmentioning
confidence: 99%
“…Minor dysmorphisms are typically featured in the craniofacial area of SZ patients. Indeed, facial asymmetries, particularly those arising along the midfacial junctions (between frontonasal and maxillary prominence derivatives), are reproducibly found in these patients (Gourion et al, 2004;Deutsch et al, 2015). Additionally, ear shape abnormalities (including adherent ear lobes, lower edges of the ears extending backward/upward, malformed ears, asymmetrical ears, or cuspidal ears) are usually observed in SZ phenotypes (Yoshitsugu et al, 2006;Akabaliev et al, 2011;Lin et al, 2012).…”
Section: Physical Anomaliesmentioning
confidence: 98%